Digital Justice and Human Security: Evaluating E-Court Reforms in Italy and Indonesia - Marco Marchetti Marchetti (Jurnal Paradigma Hukum Pembangunan, 2026)
The digital transformation of judicial systems represents a critical intersection between technological innovation and access to justice in the 21st century. This comparative study examines the implementation and impact of E-Court reforms in Italy and Indonesia—two civil law jurisdictions with divergent institutional capacities and development trajectories. Utilizing an integrated theoretical framework combining Human Security principles with Digital Governance theory, this research analyzes how judicial digitalization affects procedural transparency, case processing efficiency, and equitable access to justice.               Drawing on qualitative document analysis of legislative frameworks, judicial performance data, and policy documents from 2015-2023, the study reveals significant contextual variations in reform outcomes comparing Italy’s Processo Civile Telematico (PCT) and Indonesia’s E-Court system.             The research identifies institutional capacity, technological infrastructure, regulatory coherence, and explicit attention to digital equity as critical determinants of successful judicial digitalization. The study highlights the importance of human security-centered design approaches, addressing ethical dimensions of artificial intelligence deployment, ensuring algorithmic transparency, and maintaining hybrid access models to prevent digital exclusion. Findings suggest that technological sophistication alone cannot guarantee successful reform; rather, success depends on contextual adaptation, comprehensive capacity building, and sustained commitment to equity principles. The comparative analysis offers valuable insights for policymakers and judicial administrators in developing and developed democracies pursuing digital justice initiatives while safeguarding human security and fundamental rights.